KONSEP SISTEM EKONOMI KERAKYATAN DALAM PEMBERDAYAAN UMKM INDONESIA - Styaningrum, Farida (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.08.TAHUN.2021DO - 10.24843/EEB.2021.v10.i08.p01, 2021)
The populist economic system is based on kinship, democracy and justice encourages the Indonesian people to participate in capital ownership and control the economy. Small and medium enterprises (SMEs’) are a manifestation of the populist economy system in Indonesia, where the majority of the capital is owned by the middle class. The study was conducted using a literature study method that focuses on the concept of a populist economy system for empowering SMEs’ in Indonesia. In the current era of regional autonomy, the populist economy system for empowering SMEs’ can be realized by raising local potential in order to increase regional economic independence. Empowerment of SMEs’ based on a populist economic system must be a priority in increasing national development, because it is proven that the SME sector is able to withstand any changes in the economic climate including in conditions of economic crisis. Empowerment of SMEs’ can be carried out if there is good cooperation between the government, the community, SME actors, stakeholders and private parties. With the foundation of the ideological spirit of the People's Economy system from several parties, it will improve Indonesia's regional and national economy.